2015
DOI: 10.1021/acs.jafc.5b03386
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids as Xanthine Oxidase Inhibitors: Structure–Affinity and Structure–Activity Relationships

Abstract: The flavonoid family has been reported to possess a high potential for inhibition of xanthine oxidase (XO). This study concerned the structural aspects of inhibitory activities and binding affinities of flavonoids as XO inhibitors. The result indicated that the hydrophobic interaction was important in the binding of flavonoids to XO, and the XO inhibitory ability increased generally with increasing affinities within the class of flavones and flavonols. The planar structure and the C2═C3 double bonds of flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 53 publications
(148 reference statements)
9
126
0
4
Order By: Relevance
“…It has been reported that XOD inhibitors act as antioxidants to decrease ROS and prevent oxidative stress (Kumar et al, 2018;Lin et al, 2015;Nile et al, 2018). Herein, SA was shown to inhibit the XOD enzyme and to have moderate O −• 2 scavenging activity and a strong DPPH radical scavenging activity.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that XOD inhibitors act as antioxidants to decrease ROS and prevent oxidative stress (Kumar et al, 2018;Lin et al, 2015;Nile et al, 2018). Herein, SA was shown to inhibit the XOD enzyme and to have moderate O −• 2 scavenging activity and a strong DPPH radical scavenging activity.…”
Section: Discussionmentioning
confidence: 88%
“…Natural products including flavonoids exhibit diversified bioactivities and lower toxicity compared with classical XOR inhibitors [32]. Flavonoids have a potent inhibitive effect towards XOR both in vitro and in vivo [33], such as apigenin, luteolin, hyperin etc [34]. C2 = C3 double bonds of flavonoids contributed to their planar structure and the hydroxyl groups on C-5 and C-7 were advantageous for binding to XOR [34].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have a potent inhibitive effect towards XOR both in vitro and in vivo [33], such as apigenin, luteolin, hyperin etc [34]. C2 = C3 double bonds of flavonoids contributed to their planar structure and the hydroxyl groups on C-5 and C-7 were advantageous for binding to XOR [34]. Baicalein is a natural flavonoid with all these structure superiorities above.…”
Section: Discussionmentioning
confidence: 99%
“…A quantity of no less than 1/2 kg/day is recommended. Also black grapes and blackberries are high in the flavonoids epicatechin and catechin [53].…”
Section: ) Antioxidants Supplementationmentioning
confidence: 99%